Delphic Language:A Problem for Authors and Indexers - Riggs, Fred W. (Journal of Information and Knowledge, 1991)
Presents a new approach to naming of terms known as Onomantic approach. Provides detailed structure of this approach and its application in the fields of Information Science and Sociology. Suggests further study in these areas.